Regulation in the liberal professions in Turkey : serving the public interest or the private interests? accounting profession’s case - Moussa, Oumarou (My University, 2023)
Araştırmacılar, mesleki etik kurallarının amacı ve işleyişinin yanı sıra, ortaya çıkış nedenleri ve gerekçelerini anlamakla ilgilenmişlerdir. Mesleki etik kuralların rolü ve işlevine ilişkin eleştirel (veya özel çıkar) bakış açısı ile işlevselci (veya kamu yararı) bakış açısı arasındaki tartışma, meslek sosyolojisi literatüründe tanımlanmaktadır. Bu tez, mesleki etik kuralların muhasebe meslek kuruluşlarının disiplin süreçleri tarafından kendi özel çıkarlarını korumak yerine kamu çıkarını korumak için nasıl ve ne ölçüde uygulandığını inceleyerek, muhasebe mesleğinin etik kurallarının ve disiplin sürecinin altında yatan motivasyonu ve gizli nedenleri anlamayı amaçlamaktadır. Veriler, 2011-2020 yılları arasında İstanbul Serbest Muhasebeci Mali Müşavirler Odası (İSMMMO) Disiplin Kurulu tarafından muhasebecilere verilen 6507 disiplin suçunun içerik analizini içermektedir. Bu araştırmada, 5499 farklı ihlal türü kamu yararına işlenen suçlar ve 1008 özel yararına işlenen suçlar olarak kategorize edilmiştir. Araştırma bulguları, İstanbul muhasebe mesleğinin disiplin sürecini hem kamu yararını hem de özel yararı koruyacak şekilde işlettiğini göstermektedir. Bu araştırma, İSMMMO disiplin otoriteleri tarafından verilen nispeten az sayıdaki kararı, özellikle de özel çıkar ve kamu çıkarı suçları için verilen kararlar arasındaki ayrımı ele almaktadır. Ayrıca, bu bulgular muhasebe mesleğinin üyelerini cezalandırma konusunda isteksiz olduğunu veya disiplin uygulamalarının bir tür disiplin sembolizmi olduğunu göstermektedir.

Researchers have been interested with understanding out the purpose and functioning of professional ethical rules, as well as the reasons and justifications for their emergence. The argument between the critical-theorist (or private interest) viewpoint and the functionalist (or public interest) perspective on the purpose and function of professional ethical rules is described in literature on the sociology of professions. This thesis seeks to understand the motivation and latent motives that underpin the accounting profession's ethical rules and its disciplinary procedure through examining exactly how and to what degree professional ethical rules are enforced by the disciplinary processes of professional accounting bodies in preserving the public interest as opposed to preserving their private interests. Data includes a content analysis of 6507 disciplinary offences imposed on accountants by the disciplinary committee of the Istanbul Chamber of Certified Public Accountants (ISMMMO) between 2011 and 2020. In this investigation, 5499 different types of infractions were categorized as public-interest offences and 1008 as private-interest offences. The research finding indicate that, the Istanbul accounting profession operates its disciplinary procedure according to protect both public interest and private interest. This research addresses the relatively few decisions made by ISMMMO disciplinary authorities, specifically the distinction between rulings for private interest and public interest violations. Also, these findings suggest that the accounting profession is reluctant to punish its members or that disciplinary practices are a form of disciplinary symbolism”.
Türkiye'de liberal mesleklerde regülasyon : kamu yararına mı yoksa özel çıkarlara mı hizmet etmektedir? Muhasebe mesleği örneği
Keywords: Accounting; Accounting profession; düzenleme; Kamu yararı; Muhasebe; Muhasebe mesleği; özel çıkar; private interest; public interest; regulation; Taxation; Turkey; Türkiye; Vergilendirme